Granada de Fondo : coleccion de arte contemporaneo - Gollonet, Carlos; Centro José Guerrero, Granada (Granada : Diputatión., 2003)
Algarra, Javier ; Amat, Frederic ; Amo, Vicente del ; Angeles Ortiz, Manuel ; Arroyo, Eduardo ; Barry, Judith ; Bello, Manuel ; Brito, Vicente ; Brun, Rosa ; Campano, Miguel Angel ; Cruz-Diez, Carlos ; Dane, Bill ; Delvoye, Wim ; García Sevilla, Ferran ; Gonzalez, Curro ; Gorafe, Alejandro ; Gordillo, Luis ; Guerrero, José ; Hernandez Pijuan, Juan ; Juste, Julio ; Longobardo, Javier ; Lootz, Eva ; López Cuenca, Rogelio ; Madoz, Chema ; Matta (Roberto Antonio Sebastian Matta Echaurren) ; Misrach, Richard ; Miura, Mitsuo ; Munoz, José ; Othoniel, Jean-Michel ; Lele, Ouka ; Palazuelo, Pablo ; Perejaume ; Pérez Villalta, Guillermo ; Pinar, José ; Rivera, Manuel ; Rodriguez-Acosta, Miguel ; Romero, Pedro G. ; Serna, Ismael de la ; Sevilla, Soledad ; Solano, Susana ; Teixidor, Jordi ; Torner, Gustavo ; Torres, Francesc ; Uslé, Juan ; Vega, Carlos ; Vida, Juan ; Zabell, Simon
Per kunstenaar beperkte biog. & bibliog.
Published on the occasion of the exhibition 'Granada de Fondo' at the Centro José Guerrero in Granada, 01.05.2003-11.05.2003
boek